KONSTRUKSI LEVEL PENGETAHUAN METAKOGNITIF DALAM PEMBELAJARAN AGAMA HINDU - Putu Sabda Jayendra (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Metacognitive knowledge is an aspect in achieving the highest level of abstraction skill in knowledge. It is also the highest level in Revised Bloom Taxonomy. The knowledge construction of metacognitive level is the ability to know and realize oneself, including the skill of cognitive strategy through multi-perspective and multi-dimensional thinking. The construction of metacognitive knowledge in Hindu as subject has the urgency in order to create the character of an individual learner which do not influenced by dogmatic thinking, wise, and is able to actualize the religious order and harmonic sosio-cultural people.